Photoluminescence: Tailored Near‐Infrared Photoemission in Fluoride Perovskites through Activator Aggregation and Super‐Exchange between Divalent Manganese Ions (Adv. Sci. 7/2015). Issue 7 (July 2015) - Song, Enhai; Ye, Shi; Liu, Tianhui; Du, Peipei; Si, Rui; Jing, Xiping; Ding, Sha; Peng, Mingying; Zhang, Qinyuan; Wondraczek, Lothar
<x xml:space="preserve">Abstract</x> Tailoring near‐infrared photoluminescence through activator aggregation and super‐exchange between manganese ions in a perovskite lattice is presented by Q. Zhang, L. Wondraczek, and co‐workers in article number 1500089, challenging the classical viewpoint where divalent manganese is used only for visible photoluminescence.